2019
DOI: 10.1093/ofid/ofz101
|View full text |Cite
|
Sign up to set email alerts
|

Missed Visits Associated With Future Preexposure Prophylaxis (PrEP) Discontinuation Among PrEP Users in a Municipal Primary Care Health Network

Abstract: Background Maintaining retention in preexposure prophylaxis (PrEP) care among diverse patient populations will be needed to support PrEP’s efficacy. We characterized patterns of PrEP care retention in a US municipal primary care health network and examined whether missed visits, a metric of care retention that is easy to evaluate in clinic, are associated with subsequent discontinuation. Methods We included individuals on PrEP from July 2012 until August 2017 in the San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 40 publications
7
61
1
Order By: Relevance
“…Among the 714 who have cumulatively initiated PrEP nationwide, only 22% continue to take PrEP since 2016 [22]. These uptake and retention challenges are similar to those seen with previous adolescent trials network (ATN) studies in adolescents aged 15 to 19 years, with PrEP discontinuation during ongoing HIV acquisition risk more likely (0.82 per 10‐year increase in age) in younger individuals [23,24].…”
Section: Introductionmentioning
confidence: 66%
“…Among the 714 who have cumulatively initiated PrEP nationwide, only 22% continue to take PrEP since 2016 [22]. These uptake and retention challenges are similar to those seen with previous adolescent trials network (ATN) studies in adolescents aged 15 to 19 years, with PrEP discontinuation during ongoing HIV acquisition risk more likely (0.82 per 10‐year increase in age) in younger individuals [23,24].…”
Section: Introductionmentioning
confidence: 66%
“…Person‐time was censored during periods in which participants were disenrolled. Discontinuations/gaps were defined as 90 days without PrEP [9]. HIV seroconversions were ascertained using the SFDPH/CDC’s enhanced HIV surveillance system (eHARS), permitting collection of HIV diagnoses that occurred both within and outside of the SFDPH’s surveillance jurisdiction through mandated HIV diagnosis reporting.…”
Section: Methodsmentioning
confidence: 99%
“…Pre‐exposure prophylaxis (PrEP) is a highly effective biomedical prevention strategy when taken during periods of HIV risk [1,2]. Although PrEP persistence (sustained PrEP use over time) was high among PrEP users in clinical trials and early demonstration projects [2‐4], it has been variable among later PrEP adopters and in real‐world evaluations, with 15 to 62% of users discontinuing PrEP by six months [5‐14]. Prevention‐effective adherence is a concept which describes the importance of using PrEP during periods of HIV risk, as compared to antiretroviral therapy, for which lifelong adherence is required [15].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Indeed, a recent study conducted in San Francisco, a location with robust PrEP care, found that the most common reason for discontinuation was difficulty attending clinic visits or completing laboratory tests. 16 Technological innovations in PrEP delivery systems may help address structural and social challenges related to PrEP uptake and continuity, such as fear of discrimination on the basis of one's sexual identity, difficulty attending clinic visits, or completing laboratory testing. A recent review of advances in telehealth and PrEP care in the United States outlined 5 unique provider-to-patient delivery models.…”
Section: Introductionmentioning
confidence: 99%